Antibiotic Resistance in Pathogenic Bacteria: Mechanisms and Solutions - Jawad, Hiba Ahmed; Bardan, Rose jameel; Mohamed, Zahraa Bashar; Shaher, Alyaa Yousif; Jadaan, Ahmed Amer (American Journal of Biology and Natural Sciences, 2025)
The increasing resistance of pathogenic bacteria to the range of antibiotics produced through natural and synthetic methods is a major and catastrophic health problem around the globe. Currently, the appearance of broad-spectrum resistance in pathogenic bacteria, which curbs the clinical performance of universal antibiotics like vancomycin due to emerging vancomycin-resistant Staphylococcus aureus or extended-spectrum beta-lactamase (ESBL)-positive Pseudomonas aeruginosa strains, poses crucial healthcare challenges like raised therapy expenses, higher death rates, amplified incapacities and longer hospital stays, particularly in developing countries. Moreover, challenges like global warming or the frequent transport of travelers or livestock and goods globally drastically contribute to worldwide sharing of antibiotic-resistant bacteria populations that include resistance against an extensive range of antibiotics. The continued appearance of different mechanical resistance structures in pathogenic bacteria like genetic material alterations via mutation or obtaining conjugative genetic elements carrying resistant determinants urges the adoption of a diverse methodological configuration to elucidate the evolutionary process of broad-spectrum antibiotic resistance. Because of the extremities and complexity of the flow of resistance determinants into pathogenic bacteria, the profile of 14,871 isolates tested for resistance capabilities against 21 different antibiotics in conjunction with the demonstration of biological materials was generated through a broad exploration of antibiotic resistance mechanisms and anticipated evolutionary paths [1]. In consideration of scientific research and actual prevention strategies, the reviewed profile is structured perfectly that allows a multilateral approach for further understanding the emergences of broad-spectrum antibiotic resistance in pathogenic bacteria and planning effective prophylactic steps.